PARTICIPATION LEVEL OF COMPLETION DOCTOR PROGRAM STUDENTS OF ISLAMIC EDUCATION STUDY PROGRAMS STATE ISLAMIC UNIVERSITY OF NORTH SUMATERA - Nur Asyikin, Saiful Akhyar Lubis, Wahyuddin Nur Nasution (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2019)
Abstract: This study aims to find out how the level of participation of post-graduate students indoctoral programs in completing their studies. This type of research is qualitative with a descriptiveapproach. The source of information for this study is the Islamic Education Study Program Doctoralstudents from 2015 to 2018, the head of the Islamic Education Study Program, the Lecturer ofthe PEDI Study Program, and other Pascasarjan Staff. Data collection techniques are carried outby reducing data, presenting data, and drawing conclusions/verifications. The findings in this studyinclude: (1) The level of student participation in the Postgraduate Program of the Islamic Universityof North Sumatra in the Level of Education of the Doctoral Program, especially in the PEDI StudyProgram, experienced a cycle of ups and downs from 2016 to 2018. In 2016 there were 7 studentsenrolled as students, then in 2017 it dropped to 4, then also in 2018, it rose to 7 people. (2) Thedriving factor for women to continue their education to the doctoral level is from the factors thatexist from each person because of their needs and hobbies and high desires (3) The factors thatinfluence the female students in completing the study process are the high interest in boasting thefamily and the motivation to be better. (4) The factors that become a barrier for students in completingtheir studies are financial, family support and their status. (5) The way students face abarrier in the process of completing their studies is to strengthen the determination and confidencethat all of them can be overcome with good intentions.